EFEKTIFITAS PENERAPAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA DI KOTA PALU - Aidil, Mohamad (Katalogis, 2015)
This research aims at answering the related problem of the activities of law implementation numbered 35 in the year of 2009 about the drug in Palu town. The method of the research applied was the quantitative descriptive through data collection techniques of structured observation, questionnaires, interviews and documentations. The informant selective technique used was purposive sampling of 50 informants. The results of the research The results of the research indicate that the effectivities of the law implementation numbered 35 in the year of 2009 has not been adequate with several factors that influence it like: (1) the Law material of number 35 in the year 2009 has accommodated the drug criminal act but in fact, the drug criminal act still takes place constantly and aggressively in the field, (2) Facilities and infrastructures in exterminating the drug in Palu town have not been still adequate, and they need a special addition relating to the informational technology, and (3) the law enforcement quality and drug extermination are still minus, and communities’ awareness understanding of drug danger less helps the law enforcement. Based on the above fact, a conclusion could be drawn that the implementation of the laws numbered 35 in the years 2009 in Palu town has not been optimal yet. Therefore, the communities’ awareness of drug danger is still low that arouses many misuses of drug in Palu town.